The good, the bad and the ugly of cause marketing - Neisser, Drew (Henry Stewart Talks, 2009)
Do well by doing good, Consumers care, The triple bottom line, The six principles, Start with sincere, Avoid cause washing, Anita Roddick, A business with a cause, Dynamic founders, Product category relevance, Product attribute relevance, Target relevance, Geographic relevance, Create the compelling, Share your story, Earn your stripes campaign